Evaluation Of The Implementation Of Quality Assurance And Quality Control In Modern Housing Development in Makassar City - Noor Fadilah Romadhani; Dwi Wahyuni Aprianti (Indonesian Journal of Fundamental Sciences, 2026)
This study assesses the implementation of Quality Assurance (QA) and Quality Control (QC) in modern housing development in Makassar City, identifies obstacles affecting the effectiveness of the quality management system, and formulates strategic recommendations to enhance construction quality. A descriptive qualitative approach was employed, utilizing a case study at the Bukit Baruga Housing Complex. Data collection involved field observations, semi-structured interviews, and project documentation. Analysis was conducted using the Miles and Huberman interactive model, supplemented by Fishbone analysis to determine the root causes of quality-related issues. The findings demonstrate that QA and QC have been implemented through quality documentation, work inspections, and material examinations. Nevertheless, the effectiveness of the quality management system is limited by incomplete documentation, suboptimal material management, inadequate field supervision, and insufficient discipline in Occupational Health and Safety (OHS) practices. These challenges negatively impact construction quality control and overall project performance. The study recommends strengthening quality documentation systems, improving supervision and inspection processes, enforcing stricter OHS discipline, and adopting digital technologies to support sustainable quality management in construction. The implementation of these strategies is anticipated to enhance the effectiveness of QA and QC systems, thereby improving the quality of modern housing construction projects in Makassar City.